Geografia hotelarstwa [The Geography of the Hotel Industry], Andrzej Kowalczyk, Wydawnictwo Uniwersytetu Łódzkiego, Łódź 2000, ss. 429 - Liszewski, Stanisław (Turyzm/Tourism, 2001)
Academics representing many different fields, including geography, have become interested in hotel services as a result of their recent dynamic development. Hotels are the object of analysis in both the geography of tourism, the geography of services and urban geography. The complex character of the phenomenon raises the question of whether the geography of hotel services should become an independent study area.